MexXY multidrug efflux system of Pseudomonas aeruginosa - Morita, Yuji; Tomida, Junko; Kawamura, Yoshiaki (Frontiers in Microbiology, 2012)
Anti-pseudomonas aminoglycosides, such as amikacin and tobramycin, are used in the treatment of Pseudomonas aeruginosa infections. However, their use is linked to the development of resistance. During the last decade, the MexXY multidrug efflux system has been comprehensively studied, and numerous reports of laboratory and clinical isolates have been published. This system has been increasingly recognized as one of the primary determinants of aminoglycoside resistance in P. aeruginosa. In P. aeruginosa cystic fibrosis isolates, upregulation of the pump is considered the most common mechanism of aminoglycoside resistance. Non-fermentative Gram-negative pathogens possessing very close MexXY orthologues such as Achromobacter xylosoxidans and various Burkholderia species [e.g., B. pseudomallei and B. cepacia complexes], but not B. gladioli, are intrinsically resistant to aminoglycosides. Here, we summarize the properties (e.g., discovery, mechanism, gene expression, clinical significance) of the P. aeruginosa MexXY pump and other aminoglycoside efflux pumps such as AcrD of Escherichia coli, AmrAB-OprA of B. pseudomallei, and AdeABC of Acinetobacter baumannii. MexXY inducibility of the PA5471 gene product, which is dependent on ribosome inhibition or oxidative stress, is noteworthy. Moreover, the discovery of the cognate outer membrane component (OprA) of MexXY in the multidrug-resistant clinical isolate PA7, serotype O12 deserves special attention.